Synthesis and Liver Microsomal Metabolic Stability Studies of a Fluorine‐Substituted δ‐Tocotrienol Derivative. (11th February 2020) - Liu, Xingui; Poddar, Saikat; Song, Lin; Hendrickson, Howard; Zhang, Xuan; Yuan, Yaxia; Zhou, Daohong; Zheng, Guangrong
Abstract: A fluoro‐substituted δ‐tocotrienol derivative, DT3‐F2, was synthesized. This compound was designed to stabilize the metabolically labile terminal methyl groups of δ‐tocotrienol by replacing one C−H bond on each of the two methyl groups with a C−F bond. However, in vitro metabolic stability studies using mouse liver microsomes revealed an unexpected rapid enzymatic C−F bond hydrolysis of DT3‐F2. To the best of our knowledge, this is the first report of an unusual metabolic hydrolysis of allylic C−F bonds. Abstract : Labile allylic fluorines : In an attempt to improve the metabolic stability of δ‐tocotrienol, we designed and synthesized DT3‐F2 (1 ). However, subsequent in vitro metabolic studies using mouse liver microsomes revealed that the C−F bonds of DT3‐F2 were rapidly hydrolyzed to form the hydroxy metabolites. This unexpected C−F bond hydrolysis appeared to be enzymatic and NADPH‐independent.